Prenatal exposure to traffic-related air pollution and fetal growth in a cohort of pregnant women. Issue 10 (27th July 2012) - Iñiguez, Carmen; Ballester, Ferran; Estarlich, Marisa; Esplugues, Ana; Murcia, Mario; Llop, Sabrina; Plana, Alfredo; Amorós, Rubén; Rebagliato, Marisa
Abstract : Objectives: Scant evidence is available on effects of air pollution on longitudinally measured fetal biometry, and thus it remains unclear as to whether there are critical windows of exposure or specificity of effects. Our objective was to examine the association between exposure to nitrogen dioxide (NO2 ) during pregnancy and fetal and neonatal anthropometry in a cohort of Spanish women. Methods: Temporally adjusted land-use regression was used to estimate exposure to NO2 at home addresses. Biparietal diameter (BPD), abdominal circumference (AC), femur length (FL) and estimated fetal weight (EFW) were evaluated in each trimester by ultrasound. As neonatal outcomes, weight, length and head circumference were analysed. SD scores adjusted by gestational age, mother characteristics and fetus sex were calculated at 12, 20 and 32 weeks of gestation as well as at birth. The association between fetal growth and average exposure to NO2 in the relevant windows was investigated using regression models, adjusted for socio-demographic and lifestyle-related variables. Results: Exposure to NO2 was inversely associated with BPD, AC and EFW at week 32 and with growth in these parameters in weeks 20–32. BPD and FL were also affected earlier, at week 20. NO2 levels above the median (38 μg/m 3 ) reduced size at week 32 by around 9% in all parameters except for FL (6%). The critical windows of exposure were in early pregnancy, before 20 weeks. Exposure in this period was also inversely associated with neonatal length and head circumference. Conclusions: Maternal exposure to NO2 is associated with impaired fetal growth from mid-gestation onwards.